TINGKAT KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA SMP KELAS VIII DI SMP NEGERI 6 JEMBER, SMP AL FURQAN 1, SMP NEGERI 1 RAMBIPUJI, DAN SMP PGRI 1 RAMBIPUJI - Arifani, Nurul Hidayati; Sunardi, S; Setiawani, Susi (Department of Mathematics Education , University of Jember, 2015)
Abstract. The research aims to measure the level of creative thinking ability of math for Junior High School students in 8th year class especially in SMP Negeri 6 Jember, SMP Al Furqan 1, SMP Negeri 1 Rambipuji, and SMP PGRI 1 Rambipuji. The research methods are test with open ended problems and interview. The research shows that 2,84% students are in very high level of creative thinking, 2,84% are in high level of creative thinking, 21,49% are in the middle level of creative thinking, 29,75% are in low level of creative thinking, and 43,80% are in very low level of creative thinking among total 121 students. This shows that the creatitive thinking of math for students in 8th year class especially in SMP Negeri 6 Jember, SMP Al Furqan 1, SMP Negeri 1 Rambipuji, and SMP PGRI 1 Rambipuji are still low. Key Words: creative thinking, open ended problems